Marko Jesenšek: Prekmuriana. Fejezetek a szlovén nyelv történetéből: Budapest: Balassi Kiadó, 2010. Opera Slavica Budapestinensia. Linguae Slavicae. 230. p. - Bajzek Lukácsné, Mária (Slavia Centralis, 2020)
The paper presents a book by Marko Jesenšek in Hungarian, published in collaboration with the Department of Slavic Philology and the Balassi Publishing House. It was translated and edited by dr. Mária Bajzek and György B. Lukács.
Keywords: review; Marko Jesenšek; Prekmuriana; Slovenian; history of language; Pannonian dialect group; Prekmurje literary language